2010
DOI: 10.1109/tim.2009.2037874
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Facial Imaging Using a Static Light Screen (SLS) and a Dynamic Subject

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 30 publications
0
3
0
1
Order By: Relevance
“…Temporally encoded projection patterns require comparison of consecutive frames. Previous studies have shown that slowly moving human body parts and internal organs can be reconstructed using binary (Ackerman et al, 2002;McKeon and Flynn, 2010) and phase-shifted (Lohry and Zhang, 2014;Wang et al, 2013) temporal coding. During pilot experiments, we determined that this method is too slow to be automated for bird flight.…”
Section: Introductionmentioning
confidence: 99%
“…Temporally encoded projection patterns require comparison of consecutive frames. Previous studies have shown that slowly moving human body parts and internal organs can be reconstructed using binary (Ackerman et al, 2002;McKeon and Flynn, 2010) and phase-shifted (Lohry and Zhang, 2014;Wang et al, 2013) temporal coding. During pilot experiments, we determined that this method is too slow to be automated for bird flight.…”
Section: Introductionmentioning
confidence: 99%
“…In paper [5], the automatic image processing algorithms is introduced to deal with the reduction of noise during calibration of the camera and experimental results showed that the measurement accuracy increases considerably. Image matching technique is involved in paper [6] to match multirole biometric for 3-D facial acquisition using a static light screen and a moving object. Based on the past research, we realize that image processing algorithms plays an important role in the structured light systems, at the same time, extracting useful structure information in visual scenes is an important low-level operation in 3D information processing system to guarantee the measurement accuracy in many applications.…”
Section: Introductionmentioning
confidence: 99%
“…In paper [5], the automatic image processing algorithms is introduced to deal with the reduction of noise during calibration of the camera and experimental results showed that the measurement accuracy increases considerably. Image matching technique is involved in paper [6] to match multiprobe biometric for 3-D facial acquisition using a static light screen and a moving object.…”
Section: Introductionmentioning
confidence: 99%